Implementasi Manajemen Perubahan Pada Industri Tekstil Majalaya - Efendi, Nur (JURNAL PERSPEKTIF BISNIS, 2013)
Changes in the textile industry in Majalaya is a necessity to strengthen the competitiveness of companies. The purpose of this study is to investigate the implementation of change management in the textile industry in West Java Majalaya. This type of research is descriptive. In this study used an inductive approach with a qualitative analysis method. Collecting data using in-depth interviews and observation. Informants in this study is the textile businessman, chairman of textile employers Majalaya, and workers in the textile industry. The results showed that the implementation of change management in the textile industry in Majalaya done slowly by changing the soft part and the hard part company organization. Although running slowly, this change has been able to improve competitiveness and save a lot of textile companies in Majalaya. The results of this study concluded that the implementation of change management in the textile industry in Majalaya done through efficiency and rejuvenation machine of production, changing the culture and way of thinking internal party company.Â Keywords : Change management, soft part changes, hard part changes